Legal Measures for Promoting the Leather Industry through the Introduction of a New Economic Animal: A Comparative Study of Monitor Lizard (Varanus) and Crocodile Farm Management - haiwattananukool, kreeratikron (Law for Development Graduate Journal, 2024)
This study aims to analyze the challenges and obstacles posed by Thailand’s legal measures that hinder the promotion of monitor lizards as an economic species. Since monitor lizards are still classified as protected wildlife, their breeding, trade, and export are strictly prohibited by law. This study conducts a comparative analysis of monitor lizard farm management and crocodile farm management, as crocodiles have been legally recognized as an economic species and can be bred for commercial purposes under the Wildlife Preservation and Protection Act B.E. 2562 (2019). In contrast, monitor lizards remain protected wildlife that cannot be bred for trade, preventing farmers and leather industry entrepreneurs from utilizing this resource. Therefore, this study proposes legal reforms to facilitate the classification of monitor lizards as an economic species, using crocodile farm management as a model. To achieve this, legal amendments are necessary, particularly revisions to the ministerial regulations governing the classification of protected wildlife, to include monitor lizards under the category of protected wildlife that can be bred under controlled conditions. Additionally, standardized farm management guidelines should be established following the framework of crocodile farming to ensure sustainable economic utilization without endangering wild monitor lizard populations. These legal modifications would not only enhance the competitiveness of Thailand’s leather industry in the global market but also create new economic opportunities for farmers and entrepreneurs. Furthermore, they would support systematic wildlife conservation by shifting from wild harvesting to controlled breeding within regulated farms.